What factors influence recruitment to a birth cohort of infants with Down's syndrome?. Issue 8 (8th March 2018) - Williams, Georgina M; Neville, Patricia; Gillespie, Kathleen M; Leary, Sam D; Hamilton-Shield, Julian P; Searle, Aidan J
Abstract : Objective: To understand how to maximise recruitment of young infants with Down's syndrome (DS) into research through qualitative interviews with parents and care providers. In complex neonatal and genetic conditions such as DS, frequently diagnosed after birth, parents may go through a period of adaptation. These factors need consideration when overcoming barriers to recruitment. Participants and design: Participants, who were drawn from health professionals and volunteers working with families experiencing DS, were recruited using a purposive sampling strategy. Semistructured telephone interviews were completed with nine paediatricians, three research nurses and six family support workers. Five of those interviewed had a child with DS. The interviews were transcribed and analysed thematically. Results: A positive decision to take part in a 'from-birth' cohort study depends on factors such as the child's overall health, parent demographics (educational background and ethnicity), medical interactions that take place with the families (communication) and study logistics. The data suggest that recruitment methods need to take all these factors into consideration. Multiple recruitment methods should be considered including face to face, through parent and support groups, websites and social media. There also needs to be flexibility in the research timings to fit around the needs of the child and parents. Conclusion: Researchers need to be aware of the variable responses elicited by families to a diagnosis of DS for their baby and be sensitive to the child's current medical status. This does not preclude recruitment into studies, but to maximise uptake good communication and flexibility is essential.